2013
DOI: 10.1007/s11060-013-1083-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tumor subtype on the time from primary diagnosis to development of brain metastases and survival in patients with breast cancer

Abstract: Our group has previously published the Diagnosis-Specific Graded Prognostic Assessment (GPA) showing the prognostic factors associated with survival in patients with brain metastases (BM). The purpose of this study is to investigate the relationship of breast cancer subtype to the time interval from primary diagnosis (PD) to development of BM (TPDBM), number of BM at initial BM presentation and survival. We analyzed our previously described multi-institutional retrospective database of 865 breast cancer patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
83
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(94 citation statements)
references
References 14 publications
7
83
0
4
Order By: Relevance
“…We tested the utility of the BS-GPA for determining prognosis in cases of BM. Early detection of BM, KPS, tumor subtype and age have been reported as important prognostic factors in patients with BM from breast cancer (16)(17)(18)20), and KPS and HER2 status were shown in our study to be prognostic factors. In our patient series, actual median survival times after BM were well reflected by patients' BS-GPA scores, and thus BS-GPA was shown to be effective in predicting prognosis upon a diagnosis of BM from breast cancer.…”
Section: Discussionsupporting
confidence: 60%
“…We tested the utility of the BS-GPA for determining prognosis in cases of BM. Early detection of BM, KPS, tumor subtype and age have been reported as important prognostic factors in patients with BM from breast cancer (16)(17)(18)20), and KPS and HER2 status were shown in our study to be prognostic factors. In our patient series, actual median survival times after BM were well reflected by patients' BS-GPA scores, and thus BS-GPA was shown to be effective in predicting prognosis upon a diagnosis of BM from breast cancer.…”
Section: Discussionsupporting
confidence: 60%
“…A number of studies have reported a significantly longer survival time for patients with BM in HER2-overexpressing breast cancer (17)(18)(19). In the present analysis, a non-significantly prolonged median survival time of patients with HER2-positive disease was observed.…”
Section: Discussionsupporting
confidence: 41%
“…The time interval from the initial diagnosis of breast cancer to BM diagnosis was likely to be short in luminal B and TN types [10], while the time interval was showed to not be an independent prognosis factor for survival [27]. The relationship between the metastatic time courses and survival after BM diagnosis is still not well understood.…”
Section: Discussionmentioning
confidence: 99%